The social regulation of livelihoods in unplanned settlements in Freetown: implications for strategies of formalisation. Issue 1 (1st January 2022) - Walker, Julian; Koroma, Braima; Sellu, Sudie Austina; Rigon, Andrea
Abstract : This paper questions strategies of economic formalisation which prioritise the extension of state regulation as a means of extending access to labour protection and social protection. It draws on a research project on key livelihood systems and their associated governance arrangements in three unplanned urban settlements in Freetown, Sierra Leone. Our analysis of these fishing, and sand and stone-quarrying livelihood systems highlights the collective systems of regulation of these sectors by a range of different state and non-state actors. Reviewing the contributions of these various arrangements we suggest that, instead of focusing on formalisation as pursued primarily through the extension of state regulation, it is also crucial to explore means of working with the (informal) social arrangements through which these livelihood systems are governed.